Carbon nanotube dispersion for in-vitro applications (2017)
Carbon nanotubes (CNTs) have gained popularity due to their many characteristics which make them the promising material for biomedical applications. A major challenge when working with CNTs is the difficulty to distribute them evenly throughout liquids. This research is a comparative analysis of the dispersion of multi wall CNTs (MWCNTs) in different liquid media (distilled water, ultrapure water of type I [Milli-Q], ethanol, dimethyl sulfoxide [DMSO] and cell culture medium [RPMI-1640]) by using two different sonication techniques (probe-type sonication and ultrasonic bath sonication) as well as determining the effect of sterilization in the presence and absence of fluid before dispersion. The results indicate that the best method to achieve a CNTs dispersion is to use a probe-type sonicator as well as to sterilize the CNTs samples in the presence of fluid.